(untitled) (Research, Society and Development, 2021)
This article aims to contribute to the interdisciplinary teaching of Science and Mathematics and aims to present the process of developing an educational product, integrated by didactic sequences aimed at serving early childhood education, elementary and high school, in school space outside the classroom. This product was built by a group of teachers and students, linked to the PostGraduate Program in Science and Mathematics Teaching, to meet the demand for continuing education in a private school, where teachers of early childhood education, primary and secondary education, together with the pedagogical coordination, reported difficulties in working, in an interdisciplinary manner, the skills proposed in the National Common Curriculum Base. The work was integrated by the following stages: 1- Recognition of the school space; 2- Integration with teachers in training; 3- Presentation of the selected school space; 4- Process of elaboration of the didactic sequences; 5- Presentation of the educational product to teachers in training. The group responsible for training was divided into four subgroups (Tree group, Solo group, Toys I group, Toys II group) to account for the selected school space, a small square. As an example, here the planning carried out for the Tree group is reported. The final educational product has thirteen didactic sequences that can be replicated in other spaces. This material favors the instrumentalization of professionals in training, as it leads them to new possibilities of teaching Science and Mathematics, in other school environments, outside the classroom.